1997
DOI: 10.1038/sj.onc.1201274
|View full text |Cite
|
Sign up to set email alerts
|

Defective induction but normal activation and function of p53 in mouse cells lacking poly-ADP-ribose polymerase

Abstract: Poly-ADP-ribose polymerase (PARP) and p53 are both induced by DNA damage and each has been proposed to mediate the normal cellular response to damage. We ®nd that embryo ®broblasts from PARP-null mice have a *twofold lower basal level of p53 and that the induction of p53 in response to DNA damage or nucleotide depletion is more than twofold less than in normal mouse cells. These factors combine to decrease the induced level of the p53 protein in PARP-de®cient cells by 4 ± 5-fold, compared to normal cells. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 36 publications
7
32
1
Order By: Relevance
“…Similar data were also obtained from another human glioblastoma cell line, U87MG cells, with wtp53 status (Figure 2d). These results were consistent with previous observations using V79-derivative PARP-de®cient or PARP-null cells (Whitacre et al, 1995;Agarwal et al, 1997). These results suggested that PARP is not essential for DNA damageinduced p53 accumulation but is required for an intact p53 response after DNA damage including rapid and higher magnitude of p53 accumulation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar data were also obtained from another human glioblastoma cell line, U87MG cells, with wtp53 status (Figure 2d). These results were consistent with previous observations using V79-derivative PARP-de®cient or PARP-null cells (Whitacre et al, 1995;Agarwal et al, 1997). These results suggested that PARP is not essential for DNA damageinduced p53 accumulation but is required for an intact p53 response after DNA damage including rapid and higher magnitude of p53 accumulation.…”
Section: Discussionsupporting
confidence: 83%
“…The results of Northern blotting analysis supported this suggestion (Figure 3). The 10 h delay of WAF1 expression and its appearance at 24 h after irradiation in 3AB-treated U87MG cells (Figure 2d) recapitulated the observation with PARP-null MEFs, although the 12 h delay in adriamycin-induced WAF1 expression was suggested not to be signi®cant in a previous report (Agarwal et al, 1997). Further evidence for the involvement of PARP in regulation of p53 function was provided by the results of gel mobility shift assay.…”
Section: Discussionsupporting
confidence: 47%
“…All transfections into WiT49 and HCT116 cells were done using LipofectAMINE Plus (Invitrogen). The p53-dependent reporter construct pConALuc (19) and PODXL promoter-reporter constructs (18) were cotransfected with pRLTK (Promega). The indicated amount of CP-31398, an equivalent volume of Me 2 SO solvent, or doxorubicin (200 ng/ml) was added 24 h post-transfection, and cells were harvested 19 h later.…”
Section: Methodsmentioning
confidence: 99%
“…Homozygous or heterozygous inactivation of p53 in mice or heterozygous inactivation in humans predisposes to neoplasia, and mutation of p53 occurs in over half of all spontaneous human tumors (Donehower et al, 1992;Li and Fraumeni, 1969;Srivastava et al, 1990;Greenblatt et al, 1994). In response to DNA damage, p53 is stabilized and activated to bind to speci®c DNA sequences, where it drives the transcription of genes involved in cell cycle arrest and apoptosis (Fritsche et al, 1993;Hupp et al, 1995;El-Deiry et al, 1993;Dulic et al, 1994;Miyashita and Reed, 1995;Attardi et al, 1996;Agarwal et al, 1997). p53 is also activated in response to stimuli that do not generate broken DNA directly, including nucleotide deprivation and hypoxia (Linke et al, 1996;Graeber et al, 1996;Agarwal et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In response to DNA damage, p53 is stabilized and activated to bind to speci®c DNA sequences, where it drives the transcription of genes involved in cell cycle arrest and apoptosis (Fritsche et al, 1993;Hupp et al, 1995;El-Deiry et al, 1993;Dulic et al, 1994;Miyashita and Reed, 1995;Attardi et al, 1996;Agarwal et al, 1997). p53 is also activated in response to stimuli that do not generate broken DNA directly, including nucleotide deprivation and hypoxia (Linke et al, 1996;Graeber et al, 1996;Agarwal et al, 1997). The cell cycle is regulated at several points by p53, which is required to inhibit entry into S phase in response to either DNA damage or the arrest caused by inhibitors of microtubule assembly, and the latter function links the loss of p53 to aneuploidy (Kastan et al, 1991;Dulic et al, 1994;Cross et al, 1995).…”
Section: Introductionmentioning
confidence: 99%